Cognitive disposition to respond in postgraduate trainees of general surgery at Rawalpindi Medical University - Muhammad Waqas Raza , Maria Zubair , Mailk Irfan Ahmed , Rehan Ahmed Khan , Muhammad Waqas Raza , Maria Zubair , Mailk Irfan Ahmed , Rehan Ahmed Khan (Journal of Rawalpindi Medical College, 2020)
Introduction: Cognitive biases leading to diagnostic errors are associate with adverse outcomes and compromise patient safety and contribute to morbidity and mortality. Exploration and identification of cognitive biases have been a difficult task for the clinicians and medical educators. The literature is deficient in the identification of cognitive biases in surgical trainees. The objective of the study was to identify various cognitive biases that may negatively impact clinical reasoning skills and lead to diagnostic errors in trainees of general surgery. Materials and Methods: A quantitative study was conducted involving 48 trainees of general surgery to explore the various cognitive biases. The questionnaire was devised and consisted of ten items devised to explore five biases. .Descriptive statistical analysis was done on SPSS 20 and the respondents with score >25 were categorized as predisposed to error scores of 20-25 were taken as a borderline and overall score of <25 was insignificant for the presence of cognitive bias. Results: Premature closure was the most frequent cognitive bias found significant in 34 (70 %) of trainees followed by anchoring bias in 14 (58, 3 %) trainees. The relative frequencies of different biases are shown in Table 2. The mean score of the questionnaire was 22.7 (range 10 to 38) SD 7.2. Ten out of forty-eight (21%) trainees with a mean score of >25 showed a clear inclination toward cognitive errors whereas 11 (22%) with a score in the range of 21 to 25 were categorized as having an equivocal tendency towards committing an error, Whereas 27 (56%) with a score of less than 20 were less prone to cognitive errors. Conclusion: The two most common errors seen in the study were anchoring bias and premature closure and both are related to information gathering. A larger study is required to explore the association of cognitive bias with different specialties and experience of clinicians.